Peningkatan Hasil Zukini (Cucurbita pepo L.) Varietas Zacky Z6 Akibat Pemberian Dosis Pupuk Kotoran Ayam Dan Konsentrasi Pupuk Hayati - Tati Hartati; Nunung Sondari; Rohana Abdullah; Indriana Ulfah (Paspalum: Jurnal Ilmiah Pertanian, 2022)
Experimental research aims to study the interaction between the dose of chicken manure fertilizer and the concentration of biological fertilizer in increasing the yield of zucchini. The research was conducted for three months from March to May 2021 in Sanca Village, Ciater District, Subang Regency. Using a factorial randomized block design method consisting of two factors, the first factor is the dose of chicken manure fertilizer consisting of 4 levels, namely: 0 tons ha-1 (k0), 10 tons ha-1 (k1), 20 tons ha-1 (k2 ) and 30 tonnes ha-1 (k3). The second factor is the concentration of biological fertilizers consisting of 4 levels, namely: 0 ml L-1 (h0), 5 ml L-1 (h1), 10 ml L-1 (h2) and 15 ml L-1 (h3) repeated as many as 2 times. The results showed that the dose of chicken manure fertilizer and the concentration of biological fertilizer did not show any interaction. By independent effect, all levels of treatment with biological fertilizer concentrations did not show significant differences in fruit length, fruit diameter, weight per fruit, fruit weight per plant and fruit weight per plot at harvesting time of 34 DAP, 36 DAP and 38 DAP.